Syncretistic Religious Communities in the Near East : Collected Papers of the International Symposium "Alevism in Turkey and Comparable Syncretistic Religious Communities in the Near East in the Past and Present", Berlin, 14-17 April 1995 - Kehl-Bodrogi, Krisztina.; Kellner-Heinkele, Barbara.; Otter-Beaujean, Anke. (Numen Book Series, 1997)
This volume deals with Islamic sects in the Near East such as the Alevis (Turkey), Druzes (Libanon), Alawis (Syria), Ahl-i Haqq (Iran, Iraq) and Shabak (Iraq), which have in common a syncretistic system of belief with a strong Shi'ite influence, as well as secrecy and endogamy. The contributions in this volume focus on the present situation of these communities, their relation to mainstream Islam, their involvement in national and ethnic politics, aspects of faith and rituals, the relevance of sacred texts, modes of religious and social transformation, and the recent revival of Alevism. In view of the new visibility of these formerly "hidden" sects and their increasing social and political importance, this volume provides important information for all scholars interested in the religious and political situation of the region.